AN ANNOTATED TRANSLATION OF YOUR BABY AND CHILD, FROM BIRTH TO AGE FIVE - Sari, Wati Purnama (UG Journal, 2016)
The research aims are: (1) To find out what the problems are intranslating the book entitled "Your Baby and Child, From Birth To Age Wati Pumania SariFive" into Indonesian, (2) Toind out what the solutions are to the problems.This research used an introspective and a retrospective method. There are Fakultas Sastra, Universitas Gunadarma25 data analyzed which depicted difficulties encountered in translating a wp_sari@staff.gunadarma.ac.idtext in this research. The result showed that in translating a text the presenttranslator/ the researcher is not applying all ofthe principles oftranslationadvocated by Allan Duffand all of the strategies of translation advocatedby Chesterman. The researcher as a translator only applies 4 principles oftranslation namely, meaning, style and clarity, language influence andidiom and 14 strategies of translation namely, antonym (2 data), clausestructure change (2 data), cohesion change (2 data), culturalfiltering (2data), distribution change: expansion (1 data), explicitness change (2 data),paraphrase (2 data), explicitness change: implication (1 data), loan (2data), phrase structure (2 data), scheme change (2 data), synonym (2 data),transposition (2 data) and unit shift (1 data). Besides, the related theoriesadvocated by Larson, Baker, Nida & Taber, Newmark, Bassnett, andMunday, are really helping in solving all problems encountered. From theresearch result, the researcher suggested that to get a natural translationin translating the parenting or guide text which has many medical andparentina terms, people/ readers have to acknowledge and master theprinciples, strategies and related theories of translations.